Military adaptation in war with fear of change - Murray, Williamson (Cambridge University Press, 2011)
Military Adaptation in War addresses one of the most persistent problems that military organizations confront: namely, the problem of how to adapt under the trying, terrifying conditions of war. This work builds on the volume that Professor Williamson Murray edited with Allan Millett on military innovation (a quite different issue, though similar in some respects). In Clausewitzian terms, war is a contest, an interactive duel, which is of indeterminate length and presents a series of intractable problems at every level, from policy and strategy down to the tactical. Moreover, the fact that the enemy is adapting at the same time presents military organizations with an ever-changing set of conundrums that offer up no easy solutions. As the British general, James Wolfe, suggested before Quebec: 'War is an option of difficulties'. Dr Murray provides an in-depth analysis of the problems that military forces confront in adapting to these difficulties
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte; Strategic culture / Case studies; Tactics / Case studies; Adaptability (Psychology) / History; Military art and science / Decision making / Case studies; Operational art (Military science) / Case studies; Organizational effectiveness / Case studies; Military history, Modern / Case studies; Jom-Kippur-Krieg; Zweiter Weltkrieg; Strategie; Anpassung; Militär; Taktik; Erster Weltkrieg; Fallstudiensammlung